SOSIALISASI PENDAFTARAN TANAH DALAM PERSPEKTIF HUKUM AGRARIA UNTUK MENDORONG PERLINDUNGAN HUKUM ATAS TANAH DAN PARTISIPASI MASYARAKAT DESA PATAWANG SUMBA TIMUR - Pedo, Yustinus; Lay, Benediktus Peter; Maran, Mary Grace Megumi; Geme, Maria Theresia; Din, Teresia; Cunha, Yoachina Da (INTEGRITAS : Jurnal Pengabdian, 2025)
Land registration is an important activity that needs to be adhered to by the community because through land registration a certificate of land rights will be issued. The certificate is a proof tool that can provide protection and certainty to the land and the community as landowners. Land registration can also be carried out in all regions of the Republic of Indonesia. However, in certain areas there are still people who have not participated in registering their land. This can lead to agrarian conflicts because there is no proof of ownership / control over the land. The lack of land registration is also still found in the lives of people in Patawang Village, Umalulu District, East Sumba Regency. In response to these problems, it is necessary to conduct socialisation on land registration in Patawang Village. The aim is to increase the participation of the Patawang Village community towards land registration and encourage legal protection of land. The method used in this PKM is socialisation accompanied by discussion and questions and answers. In this activity, the PKM team conveyed information related to the legal basis of land registration, the definition of land registration, the importance of land registration, land registration organisers, the principles of land registration, land registration objects, land registration requirements, land registration stages, and the land registration system in Indonesia. Through socialisation activities, the community has an adequate understanding of land registration so that it can increase community participation in following land registration and realising legal protection of land.